2014
DOI: 10.1093/mmy/myu082
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of fungal pathogens in nodular skin lesions of cats

Abstract: In a retrospective study, we investigated 52 formalin-fixed, paraffin-embedded (FFPE) samples from cats with histologically confirmed cutaneous and subcutaneous mycoses to determine if the pathogens could be identified by molecular methods. Aim of the study was to obtain a deep understanding of the spectrum of infectious agents, which, as we hypothesized, was not available by histopathology alone. Detection of feline and fungal DNA was achieved in 92.3% and 94.2% of the samples, respectively. Most of the subcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 38 publications
0
32
0
1
Order By: Relevance
“…There were 100% concordant results between PCR and culture. The use of PCR to diagnose infectious agents in nodular lesions in cats again confirmed the usefulness of PCR, given that this can rarely be done via histological examination alone . There are two published studies evaluating PCR‐based methodology for the diagnosis of dermatophytosis from cat or dog hair .…”
Section: Diagnostic Testingmentioning
confidence: 88%
“…There were 100% concordant results between PCR and culture. The use of PCR to diagnose infectious agents in nodular lesions in cats again confirmed the usefulness of PCR, given that this can rarely be done via histological examination alone . There are two published studies evaluating PCR‐based methodology for the diagnosis of dermatophytosis from cat or dog hair .…”
Section: Diagnostic Testingmentioning
confidence: 88%
“…These findings indicate that alternariosis is by far the most common nodular fungal skin disease of cats in the United Kingdom. A recent investigation by Bernhardt et al indicated that the same situation probably occurs in cats in Germany (94). In a study by Chermette et al, Exophiala attenuata was also reported as the agent of nasal granuloma in a cat (95).…”
Section: Cats and Dogsmentioning
confidence: 91%
“…In particular, there was a lack of definitive identification of fungi to species level and only 5/15 (33%) of our dogs with OIFIs had biopsies of the skin lesions. Molecular identification techniques are becoming more widely available for identification of veterinary isolates; however, these techniques were not as widely available at the time of diagnosis in this retrospective report. Also, while broad range PCR can detect rare and unreported pathogens, PCR tests are susceptible to contamination during sampling, handling or storage of specimens, making this a potential drawback as this would increase false positives .…”
Section: Discussionmentioning
confidence: 97%